Answer: y + 1 = 2 (x -1)
Step-by-step explanation:
Point slope form is:
y - y1 = m (x - x1)
Point on the line is (1, -1) and slope is 2
m = 2
y1 = -1
x1 = 1
y - (-1) = 2 (x - 1) or y + 1 = 2 (x -1)
Answer:
8
Step-by-step explanation:
2+(3×2)=2+6=8
Area of trapezium= 1/2 × (a+b) × h
= 1/2 × (12 + 8) × 8
= 1/2 × 20 × 8
= 10 × 8
= 80 cm^3
Hope it helps you
The common rule is (x - 1, y + 3) can be used to describe the translation.
Step-by-step explanation:
Step 1:
The point J (-3, -4) becomes
(-4, -1).
In order to write the rule for translation from J to
, we subtract the x coordinate of J from
and subtract the y coordinate of J from
.
The x coordinate ![= -4-(-3) = -4+3 = -1.](https://tex.z-dn.net/?f=%3D%20-4-%28-3%29%20%3D%20-4%2B3%20%3D%20-1.)
The y coordinate ![= -1-(-4) = -1+4 = 3.](https://tex.z-dn.net/?f=%3D%20-1-%28-4%29%20%3D%20-1%2B4%20%3D%203.)
Step 2:
So from the calculations, we get that the x coordinate is subtracted by 1 i.e.
and the y coordinate is increased by 3 i.e.
.
So the common rule is (x - 1, y + 3).
Answer:
15
Step-by-step explanation: